Search for gamma-ray emission from a galactic supernova with the anticoincidence system of SPI. Issue 2 (22nd April 2022) - Caixach, M; Jean, P; Isern, J; Bravo, E
ABSTRACT: The detection of the very early gamma-emission of a Type Ia supernova (SNIa) could provide a deep insight on the explosion mechanism and nature of the progenitor. However, this has not been yet possible as a consequence of the expected low luminosity and the distance at which all the events have occurred up to now. An SNIa occurring in our Galaxy could provide a unique opportunity to perform such a measurement. The problem is that the optical flux would probably be so attenuated by interstellar extinction that it would prevent triggering the observations with gamma-spectrometers at the due time. In this paper, we analyse the possibility of using the anticoincidence system (ACS) of the spectrometer SPI on board of the INTEGRAL space observatory for detecting the early gamma-ray emission of an SNIa as a function of the explosion model and distance, as well as of pointing direction. Our results suggest that such detection is possible at about 6–12 d after the explosion, and at the same time, we can discard missing any hidden explosion during the lifetime of INTEGRAL .